SMO mutation predicts the effect of immune checkpoint inhibitor: From NSCLC to multiple cancers - Ji, Wenxiang; Niu, Xiaomin; Yu, Yongfeng; Li, Ziming; Gu, LinPing; Lu, Shun (Frontiers in Immunology, 2022)
Background: The emergence of immune checkpoint inhibitors (ICIs) is one of the most promising breakthroughs for the treatment of multiple cancer types, yet responses vary. Growing evidence points to a link between development signaling pathways-related genes and anti-tumor immunity, while the association between genomic alterations in these genes and ICIs response are waiting to be elucidated. Methods: Clinical data and sequencing data from published studies and our cohort were collected to analyze the association between SMO mutation status and efficacy of ICIs therapy in the NSCLC and pan-cancers cohort respectively. Furthermore, the correlation between SMO mutation and immunotherapeutic biomarkers such as immune cell infiltration, immune-related genes, and underlying signaling pathways were analyzed. Three mutant SMO plasmids were transfected into the cells, to explore the SMO mutation status on its expression and cell growth. Result: In the discovery NSCLC cohort, median progression-free survival in SMO_MUT was longer than the wildtype (23.0 m vs. 3.8 m, adjusted p=0.041). This finding was further confirmed in the validation NSCLC cohort (8.7 m vs. 5.1 m, adjusted p=0.013). In the pan-cancers cohort (n= 1347), a significant overall survival advantage was observed in SMO mutation patients (not reach [NR] vs. 18 m, adjusted p= 0.024). In subgroup analysis, the survival advantage of SMO_MUT against SMO_WT was prominent and consistent across gender, age, treatment type, cancer type, and Tumor Mutation Burden (TMB) status (all Pinteraction > 0.05). In vitro experiment, we found that both the mutant and the wildtype plasmid can promote the expression of SMO, but the mutant plasmids were lower than the wildtype in SMO mRNA and protein level. In CCK8 experiments, we found that mutant SMO plasmids can improve the growth of Calu-1 and PC-9 cells, but the capability was various between different mutations and cells. In further exploring, SMO mutation status was found to be related to higher TMB, more neoantigen load, more DDR mutations, higher MSI score and more CD8+ T cell infiltration. Conclusions: SMO mutation status was an independent prognostic factor, which can be used predict better clinical outcomes in ICIs treatment across multiple cancer types.